Perspective on Dating the Sumerian Great Flood and Hypothetical Reconstruction of Events - Giannini, Judith (European Journal of Applied Sciences, 2024)
The Sumerian kingship records are divided into two periods: The Mythical period that ends with the Great Flood, and the Dynastic (semi-historical and historical) period that follows. The dating of this Flood is not known in recognizable calendar years. The purpose here is to attempt to identify a likely modern calendar date and a cause precipitating the event. This is done by calibrating (to calendar years) the length of years of reign during the Mythical period, and also during the semi-historical Dynastic period (counting backward from a known historical date) to identify a range of years that most likely encompassed the Flood. That range of dates is used to identify the geophysical event that can be associated with a possible cause for the Flood, which is the basis of validating the Flood myth as being the result of a real event, not merely an ancient story with religious or political purpose. The relation between the Sumerians and Egyptian during this time is discussed.